Historical Development of the epic Mahābhārata (Patan Prospective Journal, 2023)
This research article deals with the evolution of the epic Mahābhārata in the present form. The study has its relevance to understand the historical origin of the text so that the reader could able to probe its importance in the present context. The article addresses on the research problems concerning to the historicity of Mahābhārata war, the text's stages of development, its authorship and date of production. Is the Mahābhārata war historical or fictional? Is the text written at a timer it is an evolutionary text? Who wrote it and when was it written? The article seeks answers to the aforementioned research questions by applying the methodological tool of the Marxist concept of historical materialism. The study reveals that the Mahābhārata is found to be an evolutionary text and evolves to the present form in three stages. The scholars are not unanimous regarding to the historicity of Mahābhārata war, the text's authorship and its date of production.